2021
DOI: 10.1016/j.vaccine.2021.03.034
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination attitudes, values and intentions among United States adults prior to emergency use authorization

Abstract: Introduction Safe and effective vaccines against Coronavirus Disease 2019 (COVID-19) provide the best opportunity to control the pandemic. Having safe and efficacious vaccines available is only half the equation; people must also take them. We describe a study to identify COVID-19 vaccine attitudes, values and intentions immediately preceding authorization of COVID-19 vaccines in the US. Methods A national panel survey was conducted to measure intent to receive COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
143
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(159 citation statements)
references
References 19 publications
11
143
0
5
Order By: Relevance
“…Research has demonstrated a significant association between the adoption of preventive behaviors against COVID-19 and motivation to receive a COVID-19 vaccination. However, adopting preventive behaviors did not guarantee a high motivation to receive a COVID-19 vaccination [ 30 , 31 ]. Most of the recommended preventive behaviors against COVID-19 are well-known measures to prevent the spread of respiratory infectious diseases with proven benefits; however, the COVID-19 vaccines have been developed in a short period, causing some individuals to be skeptical.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has demonstrated a significant association between the adoption of preventive behaviors against COVID-19 and motivation to receive a COVID-19 vaccination. However, adopting preventive behaviors did not guarantee a high motivation to receive a COVID-19 vaccination [ 30 , 31 ]. Most of the recommended preventive behaviors against COVID-19 are well-known measures to prevent the spread of respiratory infectious diseases with proven benefits; however, the COVID-19 vaccines have been developed in a short period, causing some individuals to be skeptical.…”
Section: Introductionmentioning
confidence: 99%
“…The result of a review study supported the effectiveness of Protection Motivation Theory, Health Belief Model, and Theory of Planned Behavior on informing infectious disease modelling, research, and public health practice [ 39 ]. Because knowledge regarding COVID-19 and protective behaviors [ 40 , 41 ] and previous experiences regarding adopting protective behaviors [ 31 ] also predict further adoption of protective behaviors against respiratory infectious diseases, they are included in the extended PMT.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations